44 Body composition may be prognostic and predictive of clinical outcomes in metastatic renal cell carcinoma (mRCC) patients treated with immune checkpoint inhibitors (ICI). (10th December 2020) - Martini, Dylan; Anders Olsen, T; Goyal, Subir; Liu, Yuan; Evans, Sean; Magod, Benjamin; Brown, Jacqueline; Yantorni, Lauren; Russler, Greta; Caulfield, Sarah; Goldman, Jamie; Nazha, Bassel; et al.
Abstract : Background: Immune checkpoint inhibitors (ICI) have revolutionized the treatment of metastatic renal cell carcinoma (mRCC). Biomarkers for mRCC patients treated with ICI are limited, and body composition is underutilized in mRCC. We investigated the association between body composition and clinical outcomes in ICI-treated mRCC patients. Methods: We performed a retrospective analysis of 79 ICI-treated mRCC patients at Winship Cancer Institute from 2015–2020. Patients with CT scans within 2 months of ICI-initiation were included. Baseline CT images were collected at mid-L3 and segmented using SliceOMatic v5.0 (TomoVision). Density of skeletal muscle (SM), subcutaneous fat, inter-muscular fat, and visceral fat were measured and converted to indices by dividing by height(m)2 (SMI, SFI, IFI, and VFI, respectively). Total fat index (TFI) was defined as the sum of SFI, IFI, and VFI. Patients were characterized as high versus low for each variable at gender-specific optimal cuts using overall survival (OS) as the primary outcome. A prognostic risk score was created based on the beta coefficient from the multivariable Cox model (MVA) after best subset variable selection. Body composition risk score was calculated as IFI + 2*SM mean + SFI, and patients were classified as high (0–1), intermediate (2), or low-risk (3–4). Kaplan-Meier method and Log-rank test were used to estimate OS and PFS and compare the risk groups. Concordance statistics (C-statistics) were used to measure the discriminatory magnitude of the model. Results: Most were male (73%), and median age was 61 years. Patients were primarily intermediate (54%) or poor-risk (30%) per IMDC criteria and most received ICI as first (35%) or second-line (51%) therapy. The body composition high-risk patients had significantly shorter OS (HR: 6.37, p<0.001), PFS (HR: 4.19, p<0.001), and lower chance of CB (OR: 0.23, p=0.044) compared to low-risk patients in MVA (table 1 ). Patients with low TFI had significantly shorter OS (HR: 2.72, p=0.002), PFS (HR: 1.91, p=0.025), and lower chance of CB (OR: 0.25, p=0.008) compared to high TFI patients in MVA. The C-statistics were higher for body composition risk groups and TFI compared to IMDC and BMI (table 2 ). The median OS and PFS were shorter for high-risk versus intermediate and low-risk patients (figures 1–2 ). Conclusions: Risk stratification using the body composition variables IFI, SM mean, SFI, and TFI may be prognostic and predictive of clinical outcomes in mRCC patients treated with ICI. Larger, prospective studies are warranted to validate this hypothesis-generating data. Acknowledgements: Research reported in this publication was supported in part by the Breen Foundation and the Biostatistics Shared Resource of Winship Cancer Institute of Emory University and NIH/NCI under award number P30CA138292. The content is solely the responsibility of the authors and does not necessarily represent the official views of the National Institutes of Health. Trial Registration: Not applicable Ethics Approval: This retrospective study was approved by the Emory University Institutional Review Board. Consent: Not applicable References: Not applicable